Waste heat recovery in heat pump systems: solution to reduce global warming - Baradey, Yehya; Hawlader, Mohammad Nurul Alam; Ismail, Ahmad Faris; Hrairi, Meftah (IIUM Press, 2015)
Energy conversion technologies, where waste heat recovery systems are included, have received significant attention in recent years due to reasons that include depletion of fossil fuel, increasing oil prices, changes in climatic conditions, and global warming. For low temperature applications, there are many sources of thermal waste heat, and several recovery systems and potential useful applications have been proposed by researchers [1-4]. In addition, many types of equipment are used to recover waste thermal energy from different systems at low, medium, and high temperature applications, such as heat exchangers, waste heat recovery boiler, thermo-electric generators, and recuperators. In this paper, the focus is on waste heat recovery from air conditioners, and an efficient application of these energy resources. Integration of solar energy with heat pump technologies and major factors that affect the feasibility of heat recovery systems have been studied and reviewed as well.